Large Efficiency Improvement in Cu2ZnSnSe4 Solar Cells by Introducing a Superficial Ge Nanolayer. Issue 21 (7th August 2015) - Giraldo, Sergio; Neuschitzer, Markus; Thersleff, Thomas; López‐Marino, Simón; Sánchez, Yudania; Xie, Haibing; Colina, Mónica; Placidi, Marcel; Pistor, Paul; Izquierdo‐Roca, Victor; Leifer, Klaus; Pérez‐Rodríguez, Alejandro; et al.
Abstract : A large improvement in Cu2 ZnSnSe4 solar cell efficiency is presented based on the introduction of a Ge superficial nanolayer. This improvement is explained by three complementary effects: the formation of a liquid Ge‐related phase, the possible reduction of Sn multicharge states, and the formation of GeOx nanoinclusions, which lead to an impressive solar cell ( V OC ) increase.